2000
DOI: 10.1007/s007050050020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism across regions of the three open reading frames of "Norwalk-like viruses"

Abstract: Genomic characterization of Norwalk-like human caliciviruses (NLVs) originating from outbreaks and sporadic cases of acute gastroenteritis has revealed surprisingly high levels of diversity, even in the RNA polymerase gene, which is anticipated to be highly conserved. Since information on antigenic relationship is limited, due to the lack of a tissue culture system for these viruses, strains mostly are described on the basis of their genetic relatedness. However, the lack of uniformly applied criteria has led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
178
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(183 citation statements)
references
References 32 publications
2
178
0
2
Order By: Relevance
“…This conserved nucleotide motif is almost identical within each genogroup of NoVs and SaVs, probably facilitating homologous recombination during co-infection of a cell by different genotypes of NoVs or SaVs within the same genogroup. In fact, recombinant NoVs having a recombination site at the RdRp-capsid junction region were identified in humans, calves and pigs [15,48,[59][60][61][62][63]. Two porcine NoVs, QW170 and QW218 strains, which share 99% nt identity at the 3'-end 3kb sequence of the genome, were reported as potential recombinants [15].…”
Section: Recombination Of Porcine Novs and Savsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conserved nucleotide motif is almost identical within each genogroup of NoVs and SaVs, probably facilitating homologous recombination during co-infection of a cell by different genotypes of NoVs or SaVs within the same genogroup. In fact, recombinant NoVs having a recombination site at the RdRp-capsid junction region were identified in humans, calves and pigs [15,48,[59][60][61][62][63]. Two porcine NoVs, QW170 and QW218 strains, which share 99% nt identity at the 3'-end 3kb sequence of the genome, were reported as potential recombinants [15].…”
Section: Recombination Of Porcine Novs and Savsmentioning
confidence: 99%
“…The majority of specific primers have been designed based on the most conserved RdRp region of the genome [29,68]. However, sequence analysis of the polymerase region of a wide range of virus strains indicated that this region is also variable with the nucleotide identity as low as 53% between strains of different genogroups and 60-64% within genogroup [59].…”
Section: Rt-pcrmentioning
confidence: 99%
“…Norovirus genotype identities are generally maintained across the open reading frames (ORFs). However, a number of norovirus strains failed to maintain their sequence identities for RNA-dependent RNA polymerase and VP1, and they were shown to be recombinant (16,20,30). Evidence suggested that the recombination site occurred at the conserved polymerase and capsid junction between ORF1 and ORF2.…”
mentioning
confidence: 99%
“…Human NVs can be divided into two genogroups, genogroups GI and GII, by genetic analysis of the RNA polymerase and capsid regions (1, 15), with several genotype classifications having been reported independently (1,16,33). Recently, based on the genotype classification of Katayama et al (16), Kageyama et al (15) reported on a detailed scheme for the genotyping of NVs based on distribution analysis by using the pairwise distance of the capsid N-terminal/shell domain.…”
mentioning
confidence: 99%